2018
DOI: 10.1039/c8cy00947c
|View full text |Cite
|
Sign up to set email alerts
|

Improved hydrothermal stability of Pd nanoparticles on nitrogen-doped carbon supports

Abstract: Carbon supports have been shown to provide better hydrothermal stability than alumina or silica supports, thus attracting more attention for aqueous-phase biomass conversion reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…1b and Supplementary Fig. 1) 19,20 . Upon carbonization at 300°C for 10 min, an additional broad signal appeared in the range between −180 and −230 ppm in the 15 N{ 1 H} CPMAS spectrum (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…1b and Supplementary Fig. 1) 19,20 . Upon carbonization at 300°C for 10 min, an additional broad signal appeared in the range between −180 and −230 ppm in the 15 N{ 1 H} CPMAS spectrum (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…1e). Fast CP build-up suggests that the new signal can be assigned to the N-H-containing species, imidazolium 19 , in which the aromatic ring contains two nitrogen atoms ( Supplementary Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…For example, the doping of nitrogen on the carboncoated SBA-15 support significantly improved the stability of Pd metal against leaching and sintering during FUR hydrogenation. [103] The N-doped mesoporous carbon-supported Ru nanoparticles showed higher stability compared to the undoped carbon support during glycerol reforming. [104] The Ndoped CNT-supported Pd nanoparticles showed stability against sintering during nitrobenzene hydrogenation reaction.…”
Section: Improving the Stability Of Supported Metal Catalystsmentioning
confidence: 96%
“…34 It was also found that the metal leaching could be inhibited effectively due to graphite encapsulation. 35 In this work, we developed a series of MNC-T (M/T: different metals/pyrolysis temperatures) catalysts and tested their catalytic performances for the conversion of 2phenoxyacetophenone. It was demonstrated that CoNC-900 presented outstanding catalytic performance in the reaction.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In addition, N-doped carbons could generate more active sites due to the tunable electron feature and improve the activity of the catalysts well. , In addition, the carbon materials enhanced the contact between the substrate and the catalyst by increasing wettability of the surface . It was also found that the metal leaching could be inhibited effectively due to graphite encapsulation …”
Section: Introductionmentioning
confidence: 99%